2016
DOI: 10.1002/admi.201500452
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Molecular Orientation in Acceptor–Donor Interfaces between Pentacene and C60 and Diels–Alder Adduct Formation at the Molecular Interface

Abstract: Interfaces between pentacene and Buckminster‐fullerene (C60) have attracted interest due to their application as oligomeric model system for organic solar cells. As the actual device characteristics in such implementations are crucially controlled by the interface structure, detailed investigations of this interface on a molecular level are mandatory. In this study, the influence of the orientation of the pentacene molecules in highly ordered crystalline bottom layers on the characteristics of such internal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 40 publications
4
42
1
Order By: Relevance
“…59 We also note that Breuer et al concurrently observed the presence of a reaction at the interface. 60 Because the DAc has a lowest unoccupied molecular orbital (LUMO) energy ∼0.16 eV shallower than C 60 , the presence of the DAc at the interface should affect device properties by preventing electrons from reaching the interface. 61 To test the effects of the DAc on device parameters, we purposefully introduced an "interlayer" of DAc by co-depositing a Tc:C 60 blend at the interface and performed an annealing series to vary the extent of the interfacial reaction.…”
Section: B Organic Photovoltaicsmentioning
confidence: 99%
“…59 We also note that Breuer et al concurrently observed the presence of a reaction at the interface. 60 Because the DAc has a lowest unoccupied molecular orbital (LUMO) energy ∼0.16 eV shallower than C 60 , the presence of the DAc at the interface should affect device properties by preventing electrons from reaching the interface. 61 To test the effects of the DAc on device parameters, we purposefully introduced an "interlayer" of DAc by co-depositing a Tc:C 60 blend at the interface and performed an annealing series to vary the extent of the interfacial reaction.…”
Section: B Organic Photovoltaicsmentioning
confidence: 99%
“…[15][16][17] In the present work, the evolution of the crystallinity of a well-ordered bimolecular heterojunction, C 60 on a single crystal surface of pentacene (C 22 H 14 ), is studied depending on the growth temperature by means of surface X-ray diffraction techniques and noncontact mode atomic force microscopy (nc-AFM). [18] The pentacene/C 60 interface has been studied widely, both experimentally [19][20][21][22][23][24] and theoretically. [18] The pentacene/C 60 interface has been studied widely, both experimentally [19][20][21][22][23][24] and theoretically.…”
mentioning
confidence: 99%
“…Pentacene (Figure 1a) and C 60 (Figure 1b) are representative p-type (donor) and n-type (acceptor) semiconducting compounds generating an exciton-dissociating interface in a prototypical organic solar cell device. [18] The pentacene/C 60 interface has been studied widely, both experimentally [19][20][21][22][23][24] and theoretically. [25][26][27][28][29][30] It was recently discovered that C 60 crystallizes in its bulk structure epitaxially by aligning the nearest-neighbor face-centered-cubic (fcc)-110 < > axis uniquely along the [110] direction of the pentacene single crystal (Pn-SC) surface.…”
mentioning
confidence: 99%
“…Note that theoretical findings are usually done under the assumption of an inert, molecularly sharp, regular, and pure PHJ (which almost never occurs in the experiments) and lack systematic verification in a representative series of the prototypical devices. For instance, the experimental evidence on the formation of a Diels-Adler adduct at the pentacene/C 60 interface was recently found [62], thus casting doubt on the above results.…”
Section: Fabrication Of CL 6 Subpc-based Heterojunctions For Photovolmentioning
confidence: 99%